2011
DOI: 10.1161/circulationaha.110.983924
|View full text |Cite
|
Sign up to set email alerts
|

Odynophagia After Atrial Fibrillation Ablation

Abstract: A 74-year-old man with hypertrophic cardiomyopathy and paroxysmal atrial fibrillation, requiring multiple cardioversions for unstable rapid ventricular rates, was referred for electric isolation of his pulmonary veins. Wide-area circumferential ablations, combined with targeting of pulmonary vein potentials, were used to electrically isolate all 4 pulmonary veins.Before ablation, a transesophageal echocardiogram was performed after induction of general anesthesia. Ablation was performed with a closed, irrigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[1][2][3] Transesophageal echo (TEE) is used commonly at the time of AF ablation procedures to exclude left atrial thrombus, define cardiac function, and in some centers to guide transseptal puncture. [4][5][6][7] Recently, Nguyen et al 8 reported a case of an esophageal hematoma as a complication after an AF ablation. This was attributed to the use of TEE during the procedure.…”
mentioning
confidence: 99%
“…[1][2][3] Transesophageal echo (TEE) is used commonly at the time of AF ablation procedures to exclude left atrial thrombus, define cardiac function, and in some centers to guide transseptal puncture. [4][5][6][7] Recently, Nguyen et al 8 reported a case of an esophageal hematoma as a complication after an AF ablation. This was attributed to the use of TEE during the procedure.…”
mentioning
confidence: 99%
“…McCall and Thomas felt that the esophageal hematoma likely occurred due to postanesthesia emesis during the recovery period in the setting of anticoagulation and was unlikely caused by unintentional thermal injury [12]. The second case, presented by Nguyen and colleagues, concluded that the esophageal hematoma was a result of local trauma from the preprocedural transesophageal echocardiogram and was exacerbated by anticoagulation therapy [13]. Of note, the more serious and more common esophageal complication from cardiac ablation is atrioesophageal fistulas which is thought to be a direct result from thermal injury [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because this is a relatively recently reported complication, 16 despite many thousands of ablative outcome data in the literature, the true incidence and risk factors are unknown. In all cases, a TEE probe was inserted.…”
Section: Article See P 701mentioning
confidence: 99%
“…In all cases, a TEE probe was inserted. In the image by Nguyen et al, 16 a TEE was used at the start of the case to examine the left atrial appendage and then removed. In this case report, there are no comments provided regarding the difficulty with TEE insertion or the degree of probe manipulation.…”
Section: Article See P 701mentioning
confidence: 99%